Lycopene Modulates Pathophysiological Processes of Non-Alcoholic Fatty Liver Disease in Obese Rats - Mariane Róvero Costa; Jéssica Leite Garcia; Carol Cristina Vágula de Almeida Silva; Artur Junio Togneri Ferron; Fabiane Valentini Francisqueti-Ferron; Fabiana Kurokawa Hasimoto; Cristina Schmitt Gregolin; Dijon Henrique Salomé de Campos; Cleverton Roberto de Andrade; Ana Lúcia dos Anjos Ferreira; Camila Renata Corrêa; Fernando Moreto (Antioxidants, 2019)
Background: The higher consumption of fat and sugar are associated with obesity development and its related diseases such as non-alcoholic fatty liver disease (NAFLD). Lycopene is an antioxidant whose protective potential on fatty liver degeneration has been investigated. The aim of this study was to present the therapeutic effects of lycopene on NAFLD related to the obesity induced by a hypercaloric diet. Methods: Wistar rats were distributed in two groups: Control (Co, n = 12) and hypercaloric (Ob, n = 12). After 20 weeks, the animals were redistributed into the control group (Co, n = 6), control group supplemented with lycopene (Co+Ly, n = 6), obese group (Ob, n = 6), and obese group supplemented with lycopene (Ob+Ly, n = 6). Ob groups also received water + sucrose (25%). Animals received lycopene solution (10 mg/kg/day) or vehicle (corn oil) via gavage for 10 weeks. Results: Animals which consumed the hypercaloric diet had higher adiposity index, increased fasting blood glucose, hepatic and blood triglycerides, and also presented in the liver macro and microvesicular steatosis, besides elevated levels of tumor necrosis factor-α (TNF-α). Lycopene has shown therapeutic effects on blood and hepatic lipids, increased high-density lipoprotein cholesterol (HDL), mitigated TNF-α, and malondialdehyde (MDA) and further improved the hepatic antioxidant capacity. Conclusion: Lycopene shows therapeutic potential to NAFLD.